ESCALATE MILK PRODUCTION: THE AMAZING ADVANTAGES OF MARMET AND ACUPUNCTURE TECHNIQUES - Dahliana,; Rika Hairunisyah,; Yunike,; Kusumawaty, Ira (International Journal of Social Science, 2022)
Mother's milk contains essential components for the growth and development of infants. Limitations of breastfeeding are often caused by the inhibition of production factors which can be minimized by applying traditional marmet and acupuncture techniques. However, information about implementing marmet techniques and acupuncture techniques on breast milk production is still not widely found. This study aims to identify and analyze marmet and acupuncture techniques on breast milk production. The purposive sampling technique was used in determining the research respondents, totaling 60 respondents were divided into two groups. 30 respondents received treatment with marmet and acupuncture techniques for 30 other respondents. The research method used was quasi-experimental with a pretest-posttest design, and the results of data collection were analyzed using the Wilcoxon test. The respondent's informed consent was signed after explaining and agreeing to be involved in the research. The results of statistical tests showed an effect of marmet techniques and acupuncture techniques on significant baby weight before and after the study. It can be concluded that the marmet technique and acupuncture technique were significantly able to encourage milk production, which was indicated by an increase in the baby's weight on the tenth day. It is necessary to increase literacy regarding the benefits of marmet techniques and acupuncture techniques through the use of social media.